Determination of the thermodynamic parameters of ionic liquid 1-propyl-3-methylimidazolium bromide by gas-liquid chromatography. (February 2019) - Zhang, Miao; Ge, Ming-Lan; Jiao, Yu-Hai; Mu, Zhao; Huang, Rui; He, Zhuang-Zhuang
Graphical abstract: Highlights: Measurements of activity coefficients at infinite dilution using GLC. The (gas-liquid) partition coefficients were calculated. The excess thermodynamic functions, enthalpies, entropies, and Gibbs energies were calculated. The solubility parameter of the IL [PMIM][Br] was determined. Selectivity and capacity for hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). Abstract: The measurements of activity coefficients at infinite dilution ( γ i ∞ ) for 33 solutes including alkanes, cycloalkanes, alkenes, aromatic hydrocarbons, acetonitrile, acetone, tetrahydrofuran, ethyl acetate, 1, 4-dioxane, chloromethanes, alcohols in the ionic liquid (IL) 1-propyl-3-methylimidazolium bromide, [PMIM][Br], were determined by gas-liquid chromatography at five temperatures at 10 K intervals in range of (323.15–363.15) K. The densities of [PMIM][Br] were measured at the temperature range from 323.15 K to 363.15 K. The gas-liquid partition coefficients, K L at infinite dilution from 323.15 K to 363.15 K and the fundamental thermodynamic functions, such as the partial molar excess enthalpies at infinite dilution ( H - i E, ∞ ), Gibbs free energies ( G - i E, ∞ ) and entropies ( T ref S - i E, ∞ ) were calculated at a reference temperature T r e f  = 298.15. The Hildebrand's solubility parameters of the IL [PMIM][Br] were also determined by the regular solution theory (RST) combined with Flory ''combinatorial'' equation. The values of selectivity and capacity for n -hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ) at T  = 323.15 K were calculated from γ i ∞ and compared to literature values for [Br]-based ILs for the same separation problems.